Evaluation in care homes and empowerment of residents - Mandič, Srna (Anthropological notebooks, 2014)
This paper discusses evaluation in care homes, with a focus on participative evaluation, which specifically aims to empower people through participation, the development of valid local knowledge and further changes in the organisational culture in care homes. After an overview of various methods generally used to assess the quality of services in care homes, we use the model of participative evaluation as a yardstick against which to examine the quality of the evaluation practices among Slovenian care homes. Firstly, a survey among managers revealed various types of evaluation used and the fact that nearly all homes use it. Secondly, in DSO Fužine (chosen as a case study), a qualitative study was performed by placing the "evaluation practice" into the local frame of awareness and by means of a focus group of residents, aiming to identify residents' perceptions of the power of their voice regarding the daily life in home, regarding various power instances and the role of evaluation practice. The overall perception of residents was they have a fair control over life in the home, a form of "direct democracy"; while these findings cannot be generalised to all homes, they certainly represent a surprising extra quality in comparison to the present "outside world" of the currently troubled Slovenian society.
Keywords: domovi za ostarele; vrednotenje; neposredna demokracija; Slovenia; Slovenija